Attention deficit hyperactivity disorder in male patients with alcohol dependence - Etik, Ç.; Taner, Y.; Taner, E.; Arıkan, Z. (Journal of Dependence, 2008)
Objective: This study aimed to investigate the symptoms of Attention Deficit Hyperactivity Disorder (ADHD) in adulthood and childhood in patients with adult alcohol dependence and to examine the sociodemographic and clinical characteristics of these cases. Method: The study included 54 patients diagnosed with alcohol dependence who were currently undergoing treatment and those who had previously received treatment and were being followed up as outpatients. ADHD was diagnosed using the Turgay Adult ADHD Diagnostic and Assessment Scale based on DSM-IV. The Wender Utah Rating Scale was used to screen for childhood ADHD symptoms. Findings: After individuals were divided into two groups according to the presence of ADHD, the mean age at onset of alcohol use (p<0.001) and the mean age at onset of regular alcohol use (p<0.01) were found to be significantly lower in the ADHD group compared to the non-ADHD group. Furthermore, childhood ADHD scores, as determined by the Wender Utah Rating Scale, were significantly higher in those diagnosed with ADHD in adulthood (p<0.001). Conclusion: Considering the severity of childhood symptoms and whether or not treatment is received, which are among the factors predicting the persistence of ADHD into adulthood, the importance of early diagnosis and treatment in childhood is highlighted in preventing the development of alcohol and substance abuse.